Methacrylic block copolymers by sulfur free RAFT (SF RAFT) free radical emulsion polymerisation. Issue 6 (12th January 2017) - Nurumbetov, Gabit; Engelis, Nikolaos; Godfrey, Jamie; Hand, Rachel; Anastasaki, Athina; Simula, Alexandre; Nikolaou, Vasiliki; Haddleton, David M.
Abstract : We demonstrate the use of sulfur free reversible addition–fragmentation chain transfer polymerisation (RAFT) as a versatile tool for the controlled synthesis of methacrylic block and comb-like copolymers. Abstract : We demonstrate the use of sulfur free reversible addition–fragmentation chain transfer polymerisation (RAFT) as a versatile tool for the controlled synthesis of methacrylic block and comb-like copolymers. Sulfur free RAFT (SF-RAFT) utilises vinyl terminated macromonomers obtained via catalytic chain transfer polymerisation (CCTP) of methacrylates as a chain transfer agent (CTA), and thus precluding adverse aspects of the RAFT such as toxicity of dithioesters. We have synthesised a range of narrow dispersity block copolymers ( Đ < 1.2) and comb-like macromolecules by employing emulsion polymerisation allowing for the preparation of relatively large quantities (∼50 g) of the above mentioned copolymers promptly and straightforwardly. Copolymers were characterised using 1 H NMR, size exclusion chromatography (SEC), thermogravimetric analysis (TGA) and matrix-assisted laser desorption/ionization time of flight mass spectroscopy (MALDI-TOF-MS) techniques.